Pretreatment of non-sterile, rotted silage maize straw by the microbial community MC1 increases biogas production. (September 2016) - Hua, Binbin; Dai, Jiali; Liu, Bin; Zhang, Huan; Yuan, Xufeng; Wang, Xiaofen; Cui, Zongjun
Highlights: Effect of microbial pretreatment on biogas production of non-sterile, rotted silage maize straw was evaluated. Microbial community maintained structure and functional stability in non-sterile condition. Biogas production yields significantly increased after microbial pretreatment. Abstract: Using microbial community MC1 to pretreat lignocellulosic materials increased the yield of biogas production, and the substrate did not need to be sterilized, lowering the cost. Rotted silage maize straw carries many microbes. To determine whether such contamination affects MC1, rotted silage maize straw was pretreated with MC1 prior to biogas production. The decreases in the weights of unsterilized and sterilized rotted silage maize straw were similar, as were their carboxymethyl cellulase activities. After 5 d pretreatment, denaturing gradient gel electrophoresis and quantitative polymerase chain reaction results indicated that the proportions of five key strains in MC1 were the same in the unsterilized and sterilized groups; thus, MC1 was resistant to microbial contamination. However, its resistance to contamination decreased as the degradation time increased. Following pretreatment, volatile fatty acids, especially acetic acid, were detected, and MC1 enhanced biogas yields by 74.7% compared with the untreated group.